Native Larvivorous Fishes vs Alien Fishes: A Comparative Study of Biological Control of Mosquito Larvae - A, Gogoi; S. P., Biswas (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Fishes as biocontrol agents were used since past few decades. Two locally available murrels species of Assam – Channa punctata and Channa stewartii have been used to observe their larvicidal efficacy during daytime and in the evening with artificial light in three different life stages - fry, juvenile and adult after 12 and 24 hr starvation providing two densities of mosquito larvae (n=50 and n=100) and compared with the three life stages of alien fish Poecilia reticulata (guppy). Larvicidal efficacy of native fishes (murrel) were found significantly higher (p < 0.05) than the exotic ones. Among three stages of native fishes, juveniles were significantly (p < 0.05) more larvicidal than the exotic ones. The rate of consumption by native fish is found to increase after 24-hr starvation than 12 hr starvation. Further, fry and juveniles of murrels are more voracious predators of mosquito larvae than the exotic fishes. Small shallow, filthy water bodies are the breeding grounds of mosquitoes and these are also natural habitats of murrels. As murrels are hardy air-breathing fish, they are easy to culture in small enclosures. Use of native fish species can minimize the adverse impacts of insecticides.